Are you talking to me? - calling laypersons in the sphere of data economy ecosystems - Knaapi-Junnila Sari; Rantanen Minna M.; Koskinen Jani (Emerald, 2022)
Purpose Data economy is pervasively present in our everyday lives. Still, ordinary laypersons' chances to genuine communication with other stakeholders are scarce. This paper aims to raise awareness about communication patterns in the context of data economy and initiate a dialogue about laypersons' position in data economy ecosystems.
Design/methodology/approach This conceptual paper covers theory-based critical reflection with ethical- and empirical-based remarks. It provides novel perspectives both for research and stakeholder collaboration.
Findings The authors suggest invitational rhetoric and Habermasian discourse as instruments towards understanding partnership between all stakeholders of the data economy to enable laypersons to transfer from subjectivity to the agency.
Originality/value The authors provide (1) theory-based critical reflection concerning communication patterns in the data economy; (2) both ethical and empirical-based remarks about laypersons' position in data economy and (3) ideas for interdisciplinary research and stakeholder collaboration practices by using invitational rhetoric and rational discourse. By that, this paper suggests taking a closer look at communication practices and ethics alike in the data economy. Moreover, it encourages clear, rational and justified arguments between stakeholders in a respectful and equal environment in the data economy ecosystems.